Pengaruh Model Pembelajaran RICOSRE terhadap Keterampilan Berpikir Kritis dan Argumentasi Siswa pada Materi Perdagangan Internasional - Muhammad Rizal Dwi Firmansyah; Ninik Indawati; Onik Farida Ni’matullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Students often experience difficulties in learning international trade material due to the large number of foreign terms and the limited use of contextual learning, which results in memorization-oriented instruction. These conditions hinder the development of higher-order thinking skills, particularly critical thinking and argumentation skills. This study aims to analyze the effect of the RICOSRE learning model on students’ critical thinking skills and argumentation skills in learning international trade. The study employed a quasi-experimental method using a pretest–posttest control group design. The research sample consisted of two Grade IX junior high school classes selected using a purposive sampling technique. The experimental class was taught using the RICOSRE learning model, while the control class received conventional instruction. Data were collected using a reasoned multiple-choice test designed to measure students’ critical thinking and argumentation skills. The data were analyzed using descriptive and inferential statistical techniques. The results indicate that students taught using the RICOSRE learning model achieved higher critical thinking and argumentation skills compared to students taught using conventional learning. These findings suggest that the RICOSRE learning model is effective in improving students’ critical thinking and argumentation skills in international trade learning. Therefore, the RICOSRE learning model can be considered an alternative instructional model to support the development of higher-order thinking skills at the junior high school level.